Praktek Pelatihan Tahsin Al-Qur’an Bagi Mahasiswa Ilmu Alquran dan Tafsir STAIN Meulaboh - Faisal, Muhammad; Fisa, Triansyah; Mairizal, T.; SH, Hendra (Pusat Penelitian dan Pengabdian Kepada Masyarakat STAIN Teungku Dirundeng Meulaboh, 2024)
Every Muslim is required to worship by reading the Qur'an, making it obligatory for them to adhere to the rules of tajweed when doing so. Failure to understand these rules correctly may lead to errors in recitation. The Qur'an and Tafsir Study Program at STAIN Meulaboh emphasizes the Qur'an as a primary learning source, placing a high demand on students to read it properly. However, some students in the program struggle with accurate recitation, highlighting the need for additional Tahsin training to enhance their skills. Throughout the implementation of these activities, students displayed great enthusiasm, with many actively participating. Furthermore, their eagerness extended beyond merely reading accurately; many expressed a strong desire to memorize the Qur'an as well.